PERLINDUNGAN HUKUM TERHADAP AHLI DALAM PERKARA TINDAK PIDANA KORUPSI - F.H. Eddy Nugroho (Universitas Katolik Indonesia Atma Jaya, 2022)
Experts are often needed in efforts to eradicate corruption, for example to calculate and explain the magnitude of state financial losses as a result of corruption. Several experts who were presented by the public prosecutor in the corruption case were actually sued in a civil manner by the defendant because they were considered to have harmed him. The problem is how is the legal protection that can be given to experts in corruption cases, from the existence of legal demands both civil and/or criminal by parties who feel aggrieved? Article 32 paragraph 1 of the United Nations Convention Against Corruption, 2003 (UNCAC, 2003) has mandated the need for legal protection for experts, but if you look at the existing laws and regulations, the Criminal Procedure Code (KUHAP) does not regulate the protection of experts, thus also with the law governing corruption and the Draft Criminal Procedure Code. Legal protection for experts which is regulated definitively can be found in Article 28 paragraph (3) of Law Number 31 of 2014, but it still contains shortcomings, so that further it needs to be regulated in the Draft Criminal Procedure Code, by reformulating Article 40 paragraph (1) and make a new formulation so that the expert cannot be prosecuted criminally or civilly for the information given in good faith and contains the truth.